Study Comparative of Parabolic and Phased Array Antenna - Thao, Le Quang; Loc, Do Quang; Tuyen, Nguyen Xuan (VNU Journal of Science: Mathematics - Physics; Vol 30 No 3, 2014)
Abstract: This report focuses on two typical radar antennas, parabolic reflectors and arrays. Computations of the far-field radiation patterns and comparison are implemented. We concentrate on how to scan a focused beam and steering the antennas using some modern techniques such as linear phased array, array tapering and discrete Fourier transform DFT are also introduced. Keywords: Far-field radiation pattern; parabolic reflector; phased array antenna; Fourier transform.